Fair use factors and the expansion of the boundary of fair dealing in Malaysia - Abdul Ghani Azmi, Ida Madieha (2016)
During the comprehensive copyright review in 2012, Malaysia incorporated the US four fair use factors into the copyright law. Unlike the Singapore 's approach, the four fair use factors are to be applied in determining the application of fair dealing for the specified purposes mentioned in the Act. Such move leads to a number of issues. First, are fair use and fair dealing concepts necessarily contradictory to each other? Or are they coterminous to each other? This paper seeks to draw a comparison between the factors taken into account by the UK courts in the determination of fair dealing and US courts in the proving of fair use with the idea of drawing commonalities between them. The paper further examines whether there are other relevant factors that are useful in the determination of legitimate use. In so doing, the paper hopes to arrive to a fair estimation as to how much have the fair use factors changed the landscape of legitimate uses in Malaysia.